Persepsi Umat Katolik terhadap Kehadiran Wisatawan (Studi Kasus di Gua Maria Sendang Jatiningsih) - Andreas Rudiyanto; Eko Sugiarto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this study was to determine the perception of Catholics towards the presence of tourists at the Sendang Jatiningsih Maria Cave, Sleman Regency, Special Region of Yogyakarta. This research method is descriptive qualitative. The results of this study, first, the perception of Catholics towards the presence of tourists is considered not to disturb the solemnity of Catholics who are worshiping at the Sendang Jatiningsih Maria Cave. Second, the majority of informants do not mind if the Sendang Jatiningsih Maria Cave is not only a place of pilgrimage but also a tourist destination. Third, there is an opportunity to develop tourism activities without reducing the sacredness of the Sendang Jatiningsih Maria Cave. Fourth, it is necessary to separate the worship area and the tourism area as the best way so that tourism activities do not interfere with worship activities at the Sendang Jatiningsih Maria Cave. The conclusion of this study is that most Catholics view the cave not only as a place of pilgrimage, but also as a tourist destination. Keyword: Catholics, Perceptions, Tourists